1979
DOI: 10.1017/s0022172400025547
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of non-cholera vibrios in various foods

Abstract: SUMMARYA study was made of the growth of three strains of non-cholera vibrio in a range of foodstuffs and of the effect of temperature and pH on their ability to grow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Following the outbreak of cholera on the airline Sutton (1974) attempted to grow the strain which was isolated from patients, on foods similar to those served on the flight: growth occurred on stuffed egg, milk-cream mix, duck and pate. A study on the growth of non 0-1 cholera vibrios in foods showed that these organisms could multiply in a range of cooked foods to levels of up to 1010/g food (Roberts & Gilbert, 1979). In this study growth of V. cholerae was most rapid in foods with an alkaline pH such as prawns, eggs and cooked mussels with pH values of 7.9, 7-85 and 7 05 respectively; these values are close to the optimum for growth of vibrios.…”
Section: Discussionmentioning
confidence: 99%
“…Following the outbreak of cholera on the airline Sutton (1974) attempted to grow the strain which was isolated from patients, on foods similar to those served on the flight: growth occurred on stuffed egg, milk-cream mix, duck and pate. A study on the growth of non 0-1 cholera vibrios in foods showed that these organisms could multiply in a range of cooked foods to levels of up to 1010/g food (Roberts & Gilbert, 1979). In this study growth of V. cholerae was most rapid in foods with an alkaline pH such as prawns, eggs and cooked mussels with pH values of 7.9, 7-85 and 7 05 respectively; these values are close to the optimum for growth of vibrios.…”
Section: Discussionmentioning
confidence: 99%
“…The 3Ј-CS of class I integrons normally carries the antiseptic resistance gene, qacE⌬1,and the sulfonamide resistance gene, sul1. It has been observed, however, that class I integrons do not always contain the entire 3Ј-CS (6,22,25,28).…”
Section: Multiple-antibiotic-resistant Isolates Of Non-o1 Non-o139mentioning
confidence: 99%
“…The 3Ј-CS of class I integrons normally carries the antiseptic resistance gene, qacE⌬1,and the sulfonamide resistance gene, sul1. It has been observed, however, that class I integrons do not always contain the entire 3Ј-CS (6,22,25,28).Class I integrons are widely present in multidrug-resistant enteropathogens (15-17) and have been identified in V. cholerae O1 strains isolated in Vietnam (8) and Albania and Italy (11), as well as in non-O1, non-O139 strains in Thailand (9). A 150-kb conjugative plasmid was found to contain class I integron in epidemic strains of V. cholerae O1 isolated in GuineaBissau (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Roberts and Gilbert (34), survival and growth of noncholera vibrios were reported in various foods. Their growth rates increased with increasing temperature.…”
mentioning
confidence: 99%